PRIMARY CARE PROBLEMS IN PATIENTS WITH CHRONIC HEART FAILURE - O. A. Shtegman (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate primary care efficacy in patients with chronic heart failure (CHF).Material and methods. Outpatients (n=139) with CHF and 35 primary care physicians were included into the study. The evaluation of drug therapy and patient awareness of the principles of non-drug CHF treatment were performed. An anonymous survey among doctors in terms of current CHF guidelines knowledge, patient information provided by physicians, and doctors’ burnout status was also carried out.Results. Only 39% and 10% of CHF outpatients received target doses of ACE inhibitors/sartans and beta-blockers, respectively. Majority of CHF outpatients and their doctors need in additional education/training. 56% of primary care physicians demonstrated an emotional burnout.Conclusion. Author considers it essential to distribute short pocket-guidelines on CHF management among primary care physicians, and to reduce the load on primary care physicians with simultaneous strengthening of their performance control.